Teacher Readiness for AI-Based Teaching Environmentat Secondary Level in AJ&K - Ashraf, Fatima; Rashid, Nosheen; Bashir, Nageena; Shaheen, Muhammad Naqeeb ul Khalil (ACADEMIA International Journal for Social Sciences, 2025)
The increasing prevalence of Artificial Intelligence (AI) into educational settings has had profound effects on the way teaching and learning happen in secondary education settings. With the growing adoption of AI-related technologies, adaptive learning platforms, and intelligent tutoring systems in classrooms, teacher preparedness in terms of effectively working with and using AI technologies becomes paramount. This paper examines the extent to which secondary-level teachers in Azad Jammu & Kashmir (AJ&K) are ready for AI integration based on their technology literacy, ability to adapt, attitude towards the use of such technologies, and the level of institutional support. Using a combination of quantitative and qualitative research methods, a survey was conducted among 280 in-service teachers across 12 districts of AJ&K and semi-structured interviews were conducted with 24 selected participants. Despite a considerable number of teachers who hold positive attitudes towards AI (67.8%), a clear lack of proficiency is observed in AI-specific technical skills (M = 2.87 out of 5.0) and ethics (M = 2.94 out of 5.0). The factors preventing teacher readiness include poor infrastructure, insufficient professional development opportunities, and lack of institutional policy frameworks for AI integration. Drawing upon findings, an empirically-based Teacher AI Readiness Framework (TAIRF) consisting of five components.